A study on health profile of workers in a battery factory with reference to lead toxicity: six months study - Singamsetty, Bhaskar; Gollapalli, Pavan Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Occupational health should aim at the promotion and maintenance of the highest degree of physical, mental and social well-being of workers in all occupations. Among the occupational diseases, diseases due to chemical agents like chemical gases, inorganic and organic dusts, metals and their compounds, chemicals and solvents constitute one important group. Workers engaged in lead industries like gasoline additives, lead based paints, ceramic glazes, plumbing of pipes are continuously exposed and are at a greater risk of lead toxicity. The present study was aimed to emphasize the health profile of workers in a battery factory and with reference to their blood lead levels and correlation with signs and symptoms of lead toxicity. Methods: A prospective cross sectional study was conducted among workers for 6 months period and health details were evaluated along with demographic data (age, duration of work, etc.) and examined for signs and symptoms of lead toxicity. Blood lead levels of the workers were estimated and correlated with other parameters like Hb%, serum creatinine. Results: Mean blood lead levels of the workers were high among the workers working for longer duration in battery fitting unit. Toxicity signs and symptoms were observed and they were attributable to lead toxicity. Few cases had audiometric disturbances and one had loss of vision. High levels of lead in blood were found to be related to hypertension and anemia among the workers. Conclusions: Heavy metal, lead is a major environmental pollutant and its toxicity continues to create health problems in several segments of the population. There is urgent need for the prevention and control of lead toxicity by strengthening the systematic screening for blood lead levels compatible with sub clinical lead toxicity and a routine case finding for hypertension secondary to lead exposure, including IEC activities at all levels.